Parking house as energy source - Novotný, Zdeněk (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
The article deals with the design of a parking house (PH) as a source of electrical energy with the concept of V2G (Vehicle-to-grid) and it investigates the energy potential of parking houses (PH) with integrated charging stations for electric vehicles (EVs). It focuses on four selected PHs in Brno and analyses different scenarios with respect to charger types, number of parking spaces and available capacity.
Keywords: V1G; V2G; electric vehicle; parking house; available capacity